Usability Studies of Faceted Browsing: A Literature Review - Fagan, Jody Condit (Information Technology and Libraries, 2010)
Faceted browsing is a common feature of new library catalog interfaces. But to what extent does it improve user performance in searching within today’s library catalog systems? This article reviews the literature for user studies involving faceted browsing and user studies of “next-generation” library catalogs that incorporate faceted browsing. Both the results and the methods of these studies are analyzed by asking, What do we currently know about faceted browsing? How can we design better studies of faceted browsing in library catalogs? The article proposes methodological considerations for practicing librarians and provides examples of goals, tasks, and measurements for user studies of faceted browsing in library catalogs.